Pengaruh Intellectual Capital, Islamicity Performance Index Pada Kinerja Bank Umum Syariah Indonesia - Isnaini, Maheswari Nur; Irsyad, Mohamad (EconBank: Journal of Economics and Banking, 2024)
Islamic Commercial Banks are experiencing quite rapid development. In its implementation, financial performance experiences ups and downs as measured by profitability ratios. There are several indicators that affect financial performance such as intellectual capital, profit sharing ratio, zakat performance ratio, and Islamic income vs non-Islamic income. This research aims to understand several indicators that affect financial performance through the proxy of return on assets in Islamic commercial banks between 2015-2023. This research uses data sources in the form of secondary data related to financial statements with quantitative methods. This research takes a population of all Indonesian Islamic commercial banks in the 2015-2023 timeframe. The sample in this research was obtained by purposive sampling method. This research data analysis technique is multiple liner regression analysis. This study found that intellectual capital has a positive effect in improving the financial performance of Islamic banks. Meanwhile, the Profit Sharing Ratio, Zakat Performance Ratio and Islamic Income ratio were unable to affect the performance of Islamic commercial banks. so that if there is an increase in these indicators, it does not increase financial performance